A calix[4]arene-modified (Pc)Eu(Pc)Eu[T(C4A)PP]-based sensor for highly sensitive and specific host–guest electrochemical recognition. Issue 2 (18th December 2018) - Dong, Jurong; Yu, Zhenning; Kong, Xia; Zhao, Shuai; Li, Xiyou; Chen, Yuting; Chen, Yanli; Jiang, Jianzhuang
Abstract : A nonenzymatic organic electrochemical sensor with ultrasensitive and specific host–guest recognition characteristics is developed based on a novel triple-decker (Pc)Eu(Pc)Eu[T(C4A)PP]. Abstract : A calix[4]arene (C4A)-functionalized (phthalocyaninato)(porphyrinato) europium(iii ) triple-decker compound (Pc)Eu(Pc)Eu[T(C4A)PP] (1 ) is firstly designed, synthesized and prepared into well-organized films using a simple solution-processing quasi-Langmuir-Shäfer (QLS) method. The QLS film of1 on an ITO (film1 /ITO) electrode, serving as a host–guest electrochemical recognition layer, is able to establish specific responses/interactions toward organic molecules with biological and drug interest including dopamine (DA), uric acid (UA), tyrosine (Tyr), tryptophan (Trp) and Acetaminophen (APAP), depending mainly on the matching degree of molecular dimensions between the analytes and the C4A cavity in addition to their chemical nature. More significantly, the film1 /ITO electrode shows a wide linear range of electrochemical detection (from 0.1 to 100 μM) to DA and APAP, with a high sensitivity of 53.0 and 94.3 μA mM −1 and a very low detection limit of 25 and 11 nM for DA and APAP, respectively, representing the best result among the nonenzymatic organic semiconductor-based biosensors. In particular, the film1 /ITO electrode exhibits excellent stability, reproducibility, high selectivity, and anti-interference nature for the detection of both DA and APAP, indicating the great potential of calix[ n ]arene macrocycle-modified tetrapyrrole rare earth sandwich compounds in the field of ultrasensitive and specific nonenzymatic sensors.